Pengenalan Awak Sarana Perkeretaapian Pada Siswa Taman Kanak-Kanak Bina Putra - Armyta Puspitasari; Adib Kurniawan; Septiana Widi Astuti (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2023)
The introduction of train-service crew members is a form of broadening the exploration of kindergarten students in getting to know the various professions that exist within the scope of railways. With the introduction of the railway facility crew, it is hoped that kindergarten students will be able to know various types of professions and the duties of each train-service crew member and expand the scientific repertoire and student experience. Community service activities were carried out at the Madiun Indonesian Railways Polytechnic and were attended by Bina Putra Kindergarten students. The introduction of the train-service crew members was carried out using the storytelling method with video media and field trips. Exploration in the field directly was also carried out in order to find out the means used by train-service crew members in a train locomotive. The activity took place enthusiastically and interactively. The results of the implementation of community service can be concluded that: (1) Bina Putra Kindergarten students increase cognitive knowledge by knowing the profession of train-service crew members and their duties, (2) Students explore the facilities used by train-service crew members directly, and (3) Increase sufficient experience in exploring various simple elements in railways.